Gauge transformations of two-component KP and mKP hierarchies. (December 2022) - Li, Yanxiu; Li, Chuanzhong
Abstract: Based on generalized Lax equations and the Sato theory on KP and mKP hierarchies derived from the basic algebra of pseudo-differential operators, Miura- and auto-Bäcklund transformations can be derived from the gauge transformations of the Lax operators. In this paper, we study the gauge transformations of two-component KP and mKP hierarchies using the two-component generalized gauge transformations of the original operators.